Legionella pneumophila induces human beta Defensin-3 in pulmonary cells - Hippenstiel Stefan; Heuner Klaus; Flieger Antje; Opitz Bastian; Schmeck Bernd; Lang Friederike; Vardarova Kremena; Scharf Stefanie; Suttorp Norbert; N'Guessan Philippe D (Respiratory Research, 2010)
Abstract Background Legionella pneumophila is an important causative agent of severe pneumonia in humans. Human alveolar epithelium and macrophages are effective barriers for inhaled microorganisms and actively participate in the initiation of innate host defense. The beta defensin-3 (hBD-3), an antimicrobial peptide is an important component of the innate immune response of the human lung. Therefore we hypothesize that hBD-3 might be important for immune defense towards L. pneumophila. Methods We investigated the effects of L. pneumophila and different TLR agonists on pulmonary cells in regard to hBD-3 expression by ELISA. Furthermore, siRNA-mediated inhibition of TLRs as well as chemical inhibition of potential downstream signaling molecules was used for functional analysis. Results L. pneumophila induced release of hBD-3 in pulmonary epithelium and alveolar macrophages. A similar response was observed when epithelial cells were treated with different TLR agonists. Inhibition of TLR2, TLR5, and TLR9 expression led to a decreased hBD-3 expression. Furthermore expression of hBD-3 was mediated through a JNK dependent activation of AP-1 (c-Jun) but appeared to be independent of NF-κB. Additionally, we demonstrate that hBD-3 elicited a strong antimicrobial effect on L. pneumophila replication. Conclusions Taken together, human pulmonary cells produce hBD-3 upon L. pneumophila infection via a TLR-JNK-AP-1-dependent pathway which may contribute to an efficient innate immune defense.